The evaluation of antioxidant activity of individual and mixture of lemongrass, curry leaves, turmeric and ginger extracts - Kay, Huck Poh; Muhammad, Norhayati; Abdullah, Norazlin; A. Talip, Balkis (UTHM, 2018)
Lemongrass (Cymbopogon citratus), curry leaves (Murrya koenigii), turmeric (Curcuma longa) and ginger (Zingiber officinale) are frequently used as ingredients in food industry. Recent researches proved these plants contain phytochemicals which contributes to antioxidant properties. However, the evaluation were done individually and rarely in mixtures. This study was conducted to examine the antioxidant properties as well as their interaction effect when mixed together. There were 18 designated formulations with various proportions obtained from Design Expert® 6.0.4. All of the extracts were freshly decocted and analyzed for antioxidant activity by 2, 2-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging assay. Lemongrass extract exhibited the highest inhibition percentage which was 95.90% followed by curry leaves (91.99%), turmeric (69.01%) and ginger extracts (63.41%). The combination extracts of turmeric-ginger, curry leaves-ginger and curry leaves-turmeric showed the synergistic interaction effects. However, the one to one ratio of lemongrass-curry leaves extracts, lemongrass-turmeric, and lemongrass-ginger extract showed antagonistic interaction effects. In conclusion, most of the plant extracts mixture in this study contributed synergistic interaction in the formulations. This indicates the potential of these mixture to be developed into food product in the future